Thinking, Feeling, Including. An Exploratory Study of Emotional Intelligence and Attitudes and Intentions Towards Inclusion Among a Sample of Irish Primary School Teachers - Kehoe, Michele Catherine (Trinity College Dublin. School of Education. Discipline of Education, 2023)
This study explores emotional intelligence and attitudes and intentions towards inclusion among a sample of Irish primary school teachers. Research has suggested that teachers? attitudes (Boyle et al., 2020; Sharma & Sokal, 2016) and their intentions to teach in inclusive classrooms (Opoku et al., 2021; Sharma & Jacobs, 2016) are critical to the implementation of successful inclusive teaching practices. This study used a three-phase exploratory sequential mixed methods design (Creswell & Creswell, 2018). Phase 1 involved the collection of qualitative data in the form of semi-structured interviews with six participants and subsequent thematic analysis (Braun & Clarke, 2022). This led to the identification of the six themes of EI Means Others, Inclusion Means Everyone, Feeling the Weight of Responsibility, Change Happens To and Around Teachers, The Missing Self, and EI and Inclusion are Interconnected. Phase 2 of the study was the integration point in which the qualitative data was used to inform the development of the quantitative measure to be tested in the following phase. In Phase 3 a sample of 120 respondents accessed the questionnaire which consisted of the Wong and Law Emotional Intelligence Scale (Wong and Law, 2002) and the Attitudes Towards Inclusion Scale and the Intention to Teach in an Inclusive Classroom Scale (Sharma & Jacobs, 2016) and other measures regarding Responsibility and Change and Training developed by the researcher. The respondents demonstrated a high level of emotional intelligence and positive attitudes to inclusion and very favourable intentions to teach in an inclusive classroom. Based on the findings of this study recommendations are made, but overall, they present a strong foundation for the continued implementation of inclusive education in Ireland.
APPROVED
Keywords: Emotional Intelligence; Inclusive Education; Attitudes; Intentions; Primary School Teachers; Ireland